Pathological diagnosis of thyroid nodules based on core needle biopsies: comparative study between core needle biopsies and resected specimens in 578 cases - Yan Xiong; Limin Yan; Lin Nong; Yalin Zheng; Ting Li (BMC, 2019)
Abstract Background Pathological diagnosis based on core needle biopsy (CNB) should be different from a resected specimen because it is difficult to apply the histological criteria established for resected specimens to CNB due to sampling limitations. A pathological classification for thyroid nodule on CNB was first proposed by the Korean Group in 2015. The objective of this study was to test the reliability and clinical value of this proposal. Methods According to the Korean proposal, the CNB diagnoses were categorized into unsatisfactory, benign, indeterminate, follicular neoplasm, suspicious for malignancy and malignant. A comparative study between the diagnoses of CNB and resected specimens was performed. Results The consistency was moderate (κ = 0.448). Combined indeterminate, suspicious for malignancy and malignant into a single group collectively referred to as "malignant" with the remaining merged into "others", CNB demonstrated a 95.93% sensitivity, 97.30% specificity, 62.07% accuracy, 99.81% positive predictive value (PPV) and 62.07% negative predictive value (NPV) for preoperative malignancy evaluation. Conclusions The Korean proposal for pathological classification of thyroid nodules on CNB is objective, operable and highly valuable.